Transnational sustainability laws and the regulation of global value chains: Comparison and a framework for analysis - Jaakko Salminen; Mikko Rajavuori (Sage, 2022)
Several corporate disclosure and due diligence laws related to the social and environmental impacts of globalized production have been enacted across the world over the last decade. While the emergence, operation and impact of such ‘transnational sustainability laws’ have already been extensively analysed, their legal operability remains poorly understood. This a significant omission because transnational sustainability laws form a novel and increasingly important attempt to conceptualize and govern the new logic of global production networks—global value chains—and their regulatory infrastructure. Against this backdrop, this article deploys a comparison of eleven recent transnational sustainability laws and develops an analytical framework to probe legally-operative conceptualizations of global value chains. By analysing how transnational sustainability laws conceptualize the value chain, the lead firm and adequate value chain governance, we argue, these instruments emerge as proxies for a legally-operative framework that better delineates the emerging law of global value chains. Thus, our analysis contributes to growing literature on the potential and limits of transnational sustainability laws as well as to the development of nascent ‘global value chain law’.